ANALISIS LAPORAN KEUANGAN PADA KOPERASI JASA KEUANGAN SYARIAH MANDIRI SEJAHTERA 02 SUNGAI APIT KABUPATEN SIAK - Dedi Fendra; La Ode Syarfan (UIR Press, 2015)
Financial report is an overview of a company's financial condition at a specific momentwhich includes balance sheet, income statement, statement of changes in capital andcash analysis reports. The research object is the entire financial report on thecooperative financial services Syariah Mandiri Sejahtera 02 Apit River of SiakRegency. Types and sources of data used are primary data and secondary data. Methodof data collection is done by observation that the direct field observation and directinterviews with the authorities. The results of this study came to the conclusion that thefinancial statements are viewed from the aspect of liquidity, profitability and solvencycriteria belonging to the solvency or leverage ratios. It shows that the financialstatements going well, because aspects of liquidity, profitability, solvency effect on thefinancial statements.